PENGARUHDIVIDEN,UTANG, STRUKTURKEPEMILIKAN TERHADAPNILAI PERUSAHAANDENGANSTRUKTURDEWAN KOMISARIS SEBAGAIVARIABEL PEMODERASI - , Dedi Kurnia, Ertambang Nahartyo, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research focuse on the topic of corporate governance mecanism and companys value. This research shows how corporate mecanism are implemented in Indonesia. Using regression analysis method, this research investigate the effect of divedend, debt, and ownership structure to companys value with the board of comisioner structure as moderating variable. Using 273 observation from non financial company that listed in BEI (Bursa Efek Indonesia/Indonesian Stock Exchange) during 2007-2009 period, this research found that there is no interaction effect between board of comissioner structure and dividen to companys value, and also found that there is no interaction effect between board comissioner structure and debt to companys value, and finally, found that there is no interaction effect between board of comissioner structure and ownership structure to companys value. The result of this study come to conclusion that corporat governance within company could not explain agency theory about bonding mecanism to reduce agency cost.